Effect of crop retention time and acidification of the feed on phytase efficacy in broiler chickens. Issue 3 (4th May 2021) - Kristoffersen, S.; Itani, K.; Benzertiha, A.; Kierończyk, B.; Kjos, N. P.; Svihus, B.
ABSTRACT: 1. An in vitro test to study the effect of pH reduction on phytic acid degradation over time for four commercial phytases was conducted. Changing the pH level affected phytate degradation over time differently for the various phytases (P < 0.05). 2. The phytase with the largest response of pH reduction in the in vitro test and a feed pH level of 4.5 was chosen for the broiler experiment. The effect of intermittent feeding, addition of 500 FYT C. braakii- derived phytase and 1% formic acid were tested in a 2 x 2 x 2 factorial arrangement. Ten pens containing 10 birds each were fed each of the treatment combinations from 15 to 36 d of age. Ad libitum fed birds had two 4-h dark periods with 2-h light in-between, while intermittently fed birds in addition had restricted access to the feed through except for four 1-h and one 2-h feeding bouts. 3. In addition to assessing performance, excreta were collected on a pen basis. The tibia and contents from jejunum and ileum were collected from one bird per pen. In addition, crop contents were collected from the intermittently fed birds 80, 160 and 240 min after the start of feeding. 4. Phytase improved performance, ileal and jejunal P digestibility, P retention and tibia ash and P concentration (P < 0.001). Intermittent feeding increased jejunal P digestibility and P retention (P < 0.001), but ileal P digestibility increased only in the intermittently fed birds compared to the ad libitum fed birds without phytase addition (P = 0.025). Acidification increased jejunal P digestibility only in the ad libitum fed birds (P = 0.019). There was a considerable inositol hexakisphosphate degradation into lower isomers in the crop after 80 min for diets with phytase (InsP3 and 4 :P < 0.001), and acidification further increased this degradation (InsP4 :P = 0.007). After 160 min retention time, the effect of phytase and acidification was even higher with more significant (P < 0.05) interactions. 5. The current data showed that prolonged retention time in the crop combined with feed acidification increased phytase efficacy by improving the phytate degradation.